Seed set and xenia effects on grain iron and zinc density in pearl millet - Rai, Kedar N.; Govindaraj, Mahalingam; Pfeiffer, Wolfgang H.; Sambasiva Rao, A (Wiley, 2015)
Three types of seed samples (selfed, sibbed and open pollinated) can be used for mineral analysis in pearl millet [Pennisetum glaucum (L.) R. Br.] and other cross‐pollinated crops. Cost effectiveness and reliability of mineral estimates in these types of seed samples have a direct bearing on breeding efficiency. Three sets of experiments using a diverse range of materials were conducted to examine the potential use of selfed and open pollinated (OP) seed samples for the analysis of grain Fe and Zn density in pearl millet. The results of this study showed that reduction in seed set under selfing, a genotype‐dependent typical trait of this crop, led to significant and large overestimates of Fe and Zn density, indicating that selfed seeds cannot be used for reliable estimation of grain Fe and Zn density. There was no significant difference between the sibbed and crossed seeds, indicating that there was no xenia effect. Differences among the sibbed and OP seeds for Fe, Zn, and Al density were small in magnitude and not always significant, indicating that dust contamination was not a significant factor determining Fe and Zn density. Since production of OP seed is most cost effective, it can be used for reliable estimation of Fe and Zn density when dealing with a large number of breeding lines, thereby enhancing the breeding efficiency for these micronutrients in pearl millet.